1999
DOI: 10.1016/s1071-3581(99)90019-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of myocardial perfusion reversibility by rest-nitroglycerin Tc-99m-MIBI: comparison with Tl-201 reinjection

Abstract: Our data suggest that the use of an NTG MIBI protocol results in an incremental improvement for detecting exercise-induced perfusion defect reversibility and achieves results similar to those from a TI-201 reinjection protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…[12324] Nitroglycerine is known to increase blood flow in the hypoperfused myocardium and reduce regional ischemia of the heart muscle in coronary artery disease. [24589] Our study confirms these findings; we found statistically significant improvement of myocardial perfusion after nitroglycerine administration in hypoperfused areas seen at rest myocardial perfusion study. However, previous studies did neither pay much attention nor analyze areas with decreased tracer uptake at MPS with nitroglycerine vis-à-vis rest MPS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[12324] Nitroglycerine is known to increase blood flow in the hypoperfused myocardium and reduce regional ischemia of the heart muscle in coronary artery disease. [24589] Our study confirms these findings; we found statistically significant improvement of myocardial perfusion after nitroglycerine administration in hypoperfused areas seen at rest myocardial perfusion study. However, previous studies did neither pay much attention nor analyze areas with decreased tracer uptake at MPS with nitroglycerine vis-à-vis rest MPS.…”
Section: Discussionsupporting
confidence: 87%
“…[2][3][4] Numerous studies have demonstrated that 99m Tc Sestamibi myocardial perfusion scintigraphy (MPS) with nitroglycerine has similar results with nitrate-enhanced 201 Tl restredistribution for estimation of myocardial viability, prediction of functional improvements, remodeling, and survival after revascularization in patients with ischemic heart disease. [3][4][5][6] Some authors have concluded that nitroglycerine infusion during 201 Tl imaging is a useful technique for detecting underperfused, viable myocardium, requires less time to perform than rest/ redistribution imaging, and may allow detection of viable myocardium with a single 201 Tl single-photon emission computed tomographic (SPECT) study. They concluded that 201 Tl SPECT with nitrate-augmented redistribution has significant logistical and economic advantages over traditional delayed redistribution with 201 Tl reinjection.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has also been reported that MIBI is able to visualise viable tissue, 201 Tl rest-redistribution imaging remains the most widely performed method for the detection of myocardial viability in the daily routine of many centres [1,2]. Since the uptake mechanism of MIBI does not allow significant redistribution in myocardial tissue, approaches aiming to investigate different viability protocols with this tracer have been of a methodological or interventional nature, involving, for example, tracer infusion or nitrate administration [3,4,5,6,7]. Cameron et al demonstrated favourable haemodynamic and metabolic effects of hyperbaric oxygen (HBO) in myocardial infarction [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various nuclear medicine studies have addressed the effect of nitroglycerine on the detection of myocardial perfusion abnormalities. It appears that nitroglycerine may improve the detection of perfusion defects by nuclear medicine stress studies [29]. It remains unclear to what extent nitroglycerine affects the detection of perfusion abnormalities on cardiac CT studies at rest.…”
Section: Discussionmentioning
confidence: 99%